Machining and characterization of holes machined on a biomaterial Ti-6Al-4V ELI using an indigenously developed electrochemical machining cell with IEG control mechanism. Issue 3 (4th May 2022) - Aravind, S; Hiremath, Somashekhar S
Abstract: This article presents a comprehensive study on the machining and characterization of the holes machined on a biomaterial Ti-6Al-4V ELI of 350 µm thickness with hollow stainless steel tool electrode of outside diameter 250 µm using the tailor-made µ-ECM experimental setup. The distinct feature of the experimental unit is an indigenously made pulse generator circuit and a closed-loop tool feed circuit made from a current-based sensor to retain a constant inter-electrode gap (IEG) between the tool electrode and the workpiece electrode during the machining operation. The machining process parameters are electrolyte concentration (wt % C), voltage (V) and duty factor (% DF). The output responses of interest are Circularity (C), Material Removal Rate (MRR), Taper Angle (TA), Stray Corrosion Zone (SCZ) Width and Radial Over Cut (ROC) of the hole machined. The maximum MRR obtained is 7.2 µg/s at the parametric combination of 12 V, 15 wt % C and 50% DF. The maximum circularity of 0.989 and minimum SCZ width of 309.796 µm is produced by the combination of 8 V, 15 wt % C and 30% DF. The minimum ROC of 181.091 µm is generated by the combination of 10 V, 20 wt % C and 50% DF. The combination of 12 V, 25 wt % C and 40% DF resulted a minimum TA of 0.235 degrees. The machined hole topography study based on the High Resolution Scanning Electron Microscope (HRSEM) images of all the machined holes revealed that the parametric combination of 8 V, 15 wt % C and 30% DF yielded uniform microstructure in the SCZ no pitting corrosion, smooth and precise hole edge. The presence of sodium and bromine is found in Energy Dispersive Spectroscopy (EDS) analysis of the machined hole surface. In addition to these elements, titanium and vanadium are found in the used tool electrode.